2021
DOI: 10.1155/2021/9933331
|View full text |Cite
|
Sign up to set email alerts
|

Improving Fibrin Hydrogels’ Mechanical Properties, through Addition of Silica or Chitosan-Silica Materials, for Potential Application as Wound Dressings

Abstract: Fibrin is a protein-based hydrogel formed during blood coagulation. It can also be produced in vitro from human blood plasma, and it is capable of resisting high deformations. However, after each deformation process, it loses high amounts of water, which subsequently makes it mechanically unstable and, finally, difficult to manipulate. The objective of this work was to overcome the in vitro fibrin mechanical instability. The strategy consists of adding silica or chitosan-silica materials and comparing how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…Application of nanostructuration methods allowed us to generate three-dimensional cylinder-type structures that were used to repair the mandible defects generated in an animal model. Although the biomechanical properties of these bioartificial structures were lower than those of mineralized bone [29], we found that the biomechanical behavior of our tissue substitutes was high compared to previously reported values for fibrin-based hydrogels [30]. Most likely, application of the biofabrication methods described in the present work-including nanostructuration and modification of the three-dimensional structure of the biomaterial to generate a rod-shaped cylinder-was able to improve the biomechanical properties of this type of biomaterial, as previously suggested [31].…”
Section: Discussioncontrasting
confidence: 56%
“…Application of nanostructuration methods allowed us to generate three-dimensional cylinder-type structures that were used to repair the mandible defects generated in an animal model. Although the biomechanical properties of these bioartificial structures were lower than those of mineralized bone [29], we found that the biomechanical behavior of our tissue substitutes was high compared to previously reported values for fibrin-based hydrogels [30]. Most likely, application of the biofabrication methods described in the present work-including nanostructuration and modification of the three-dimensional structure of the biomaterial to generate a rod-shaped cylinder-was able to improve the biomechanical properties of this type of biomaterial, as previously suggested [31].…”
Section: Discussioncontrasting
confidence: 56%
“…Both compositions showed a gel-like behavior with the storage modulus (G’) higher than the loss modulus (G’’) for the range of frequencies investigated. The elastic modulus at 1 Hz ( Figure 3 d) was obtained from the storage modulus as described in the materials and methods section, assuming a Poisson’s ratio of 0.5 [ 23 , 24 ]. Three-dimensional hydrogels showed an average elastic modulus of 64 ± 7 Pa, while an average value of 23 ± 1 Pa was obtained for 3D BM hydrogel samples.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has explored the addition of biomaterials like genipin, which used in concentrations of 0.1%–0.5%, improved structural and biomechanical properties of NFAH ( Campos et al, 2018 ). A different approach could be the addition of 0.7 mg/ml chitosan-silica which has been shown to improve the mechanical stability of fibrin hydrogels with low risks of cytotoxicity ( Becerra et al, 2021 ). Nevertheless, “ in vivo ” studies are still needed to check efficacy and security of either option.…”
Section: Discussionmentioning
confidence: 99%